Calidad de servicio y su relación con la satisfacción del cliente en la agencia de Viajes Travel Tours Iquitos, 2022 - Malafay Vasquez, Melissa Alessandra (2023)
The objective of this study is to determine the relationship between service quality and customer satisfaction in travel agencies. Viajes y Tours, Iquitos 2022. Depending on the scope or purpose of the study, this study is quantitative - descriptive, interrelated since its objective is to evaluate the quality of the service and customer satisfaction. the Pearson correlation of the data collected with the survey is 0.862**; This indicates that variable 1 and variable 2 have a significant positive relationship, and instead has a sigma value (bilateral) of 0.000, which indicates how important it is, based on the value obtained, and it can be said that the hypothesis is acceptable. There is a significant relationship between the quality of service and customer satisfaction in travel agencies.